Synthesis and Biological Activities of 2-[3-(4-Morpholino)propylthio]-5-(difluromethoxy)benzimidazole Derivatives - Cheng, Weiming; Tan, Rihong; Zeng, Yongchi; Huang, Wei; Zhang, Wenting (Asian Journal of Chemistry, 2012)
Benzimidazole derivatives exhibit some important pharmacological actions in animals and human beings. The synthesis and pharmacological effects of two novel synthesized compounds, 2-[3-(4-morpholino)propylthio]-5-(difluromethoxy)benzimidazole (BM1) and 2-[3-(4-morpholino)ethylthio]-5-(difluromethoxy)benzimidazole (BM2), were described in this work. The tests showed that BM1 had better antiinflammatory effect than aspirin and better analgesia activity than indomethacin, while these two compounds had lower side effect of gastric ulcer than aspirin. Therefore, BM1 was an ideal antiinflammatory compound for further development.